2017
DOI: 10.1186/s12906-017-1751-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solvents extraction on phytochemical components and biological activities of Tunisian date seeds (var. Korkobbi and Arechti)

Abstract: BackgroundThe interest in natural antioxidants, especially polyphenols, is growing more and more thanks to their positive contribution to human health. Thus, the prevention from the harmful action of oxidative stress which has been involved in many diseases such as cancer, inflammation diabetes, and cardiovascular illness.Recent research proved the bioactive compounds richness of date seeds which could be a good biological matrix of natural antioxidants. Unfortunately, an important quantity of Tunisian dates s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
92
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(105 citation statements)
references
References 46 publications
8
92
2
3
Order By: Relevance
“…However, the IC 50 values with regards to different solvents used for extraction was as follows: acetone > ethyl acetate > ethanol > methanol. The results are similar to that reported by [17,27], where by a lowest DPPH radical-scavenging activity of a plant extract had the highest IC 50 .…”
Section: Antioxidant Activitysupporting
confidence: 90%
“…However, the IC 50 values with regards to different solvents used for extraction was as follows: acetone > ethyl acetate > ethanol > methanol. The results are similar to that reported by [17,27], where by a lowest DPPH radical-scavenging activity of a plant extract had the highest IC 50 .…”
Section: Antioxidant Activitysupporting
confidence: 90%
“…Roasting increases the level of caffeine, amount of flavonoids, and antioxidant capacity in dates [13]. Aqueous extracts of date seeds contain higher amount of total phenolics and flavonoids than any other extract type [14].…”
Section: Discussionmentioning
confidence: 98%
“…Fractionation solvent affects phytochemical content and biological activities. 20 The present study revealed that fractionation separated certain parts of M. pendens secondary Journal of Dentistry Indonesia 2019, Vol. 26,No.…”
Section: Discussionmentioning
confidence: 53%
“…This result agrees with the previous study by Sudiono et al 8 Methanol is known as a magic solvent because The various chemical structures and polarities result in a wide range of fractionation solvents (water, methanol, ethyl acetate, and hexane). 20 Fractionation could separate the bioactive compound from the extract and increase its purity. 21 Therefore, fractionation is expected to increase biological activities.…”
Section: Discussionmentioning
confidence: 99%